Intestinal decolonization of Enterobacteriaceae producing extended-spectrum β-lactamases (ESBL): a retrospective observational study in patients at risk for infection and a brief review of the literature. Issue 1 (December 2015) - Rieg, Siegbert; Küpper, M.; de With, Katja; Serr, Annerose; Bohnert, Jürgen; Kern, Winfried
Abstract Background Multidrug-resistantEscherichia coli and other enteric bacteria producing extended-spectrum β-lactamases (ESBL) have emerged as an important cause of invasive infection. Targeting the primary (intestinal) niche by decolonization may be a valuable approach to decrease the risk of relapsing infections and to reduce transmission of ESBL-producing enteric pathogens. Methods In a retrospective observational study we evaluated the efficacy of intestinal decolonization treatment using orally administered colistin or other non-absorbable agents given for 2 to 4 weeks in adult patients with previous relapsing infection and persistent intestinal colonization with ESBL-positiveEnterobacteriaceae (ESBL-E). Eradication success was defined as negative rectal swab or stool culture at the end of treatment and at follow up-2 weeks after treatment discontinuation. Results First-line decolonization treatment led to eradication of ESBL-E in 19/45 patients (42 %, 7/18 low-dose [4 × 1 million units] colistin, 3/12 high-dose [4 × 2 million units] colistin, 9/15 rifaximin [2 × 400 mg]), and secondary/salvage treatment was successful in 8/13 patients (62 %, 20 treatment episodes). Late follow-up showed that 7/13 patients (54 %) with successful initial or salvage decolonization became recolonized within 3 months after post-treatment assessment while all eight of the patients failing initial or salvage decolonization treatment with late follow-up remained colonized. A narrative review of the literature confirms the limited efficacy of non-absorbable antibiotics including conventional selective digestive tract decolonization (SDD)-like combination regimens for eradicating multidrug-resistant enteric bacteria from the intestinal tract. Conclusions At present, there is no clear evidence of a significant decolonization efficacy using single-drug treatment with oral non-absorbable antibiotics. More effective regimens are needed and a better definition of at risk patients is required for planning meaningful randomized controlled studies in this field.